Bifocal Vision Novalis' Philosophy of Nature and Disease - Neubauer, John (UNC Studies in the Germanic Languages and Literatures, 1971)
Relying on an edition of Novalis' notebooks which includes much of the author's scientific and philosophical musings, Neubauer's study evaluates Novalis' outline for a creative science and philosophical background of the eighteenth century. Concentrating on his study of physiology and medicine, this work illuminates Novalis' changing perspectives on the relationship between the imagination and the material world, and whether a synthesis between the two is possible.